EVEKTIFITAS PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PRESTASI BELAJAR BAHASA INDONESIA PADA SISWA KELAS II SD N KRAPYAK WETAN BANTUL - Imro’atul Mufidah; Siti Maisaroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to test the effectiveness of problem based learning in order to improve student learning achievement in Indonesian language subjects in grade II students of SD N Krapyak Wetan Bantul, the type of research used by the researcher in this study is the Quasi-experimental method with the Nonequivalent Control Group Design. This study covers two classes, namely the control class that applies teacher-centered learning and the experimental class that uses problem-based learning. The research sample that the researcher took included Class II A consisting of 25 students as the control group and Class II B consisting of 26 students as the experimental group, Test questions in the form of pre-test questions, post-test questions and documentation are data collection techniques and independent sample t-test is data analysis. Then after implementing learning with Problem Based Learning there was a significant increase in student learning achievement, in the control class the average post-test results were only 62.52, in the experimental class there was a very significant increase with the average post-test results reaching 77.38. Based on data analysis with hypothesis testing using independent sample t-test, a significance value (2-tailed) of 0.000 <0.05 was obtained, which means H0 is rejected and H1 is accepted. Thus, it is concluded that Problem Based Learning is effective in improving learning achievement in Indonesian Language Lessons for grade II students at SD N Krapyak Wetan Bantul.